Konsep Tik Sebagai Media Pembelajaran Pendidikan Agama Islam Berbasis Aplikasi - Suhirman, Suhirman; Albetrik Meizontara; Purwanto, Purwanto; Rizki Febriansyah (CV. Ulil Albab Corp, 2024)
This study aims to analyze ICT as a medium for learning Islamic Religious Education, the type of research used is literature. The results of the study: Information and Communication Technology is very important to improve the development of educational materials because it gives teachers access to various tools, applications and platforms. Types of Islamic Religious Education Learning Application Media that can be used are: Youtube, Instagram, Facebook, Whatssapp, Google Form, Zoom Meeting, Google Classroom, and Google Meet Media. Application-based ICT has several advantages such as: (1) Allows students to learn independently, (2) Flexible learning time and place, (3) Increases student activity and creativity in developing their thinking, (4) Helps strengthen learning activities so that they can stimulate and motivate students, (5) Supports the process of interaction between teachers or tutors with students, (6) Organizes the learning process more effectively. The Disadvantages of ICT as a Learning Application Media: (1) There is often misuse of technology by students. (2) The use of the web is often difficult to access. (3) the delivery of information by educators verbally is not very clear. In this increasingly advanced digital era, information and communication technology (ICT) can be an important tool in developing Islamic education. The use of ICT in Islamic education can help expand the reach of education, can help improve administrative efficiency, and can help students gain access to learning materials